THE VARIOUS MEANINGS OF CERTAIN ARABIC TRILITERAL AUGMENTED VERBS CONTAINING TWO OR THREE ADDITIONAL LETTERS - Umarali Gafforov (International Journal of Literature and Language Studies, 2026)
The Arabic language stands out among the world's languages for its richness of vocabulary, expressive power, semantic features and charm. Arabic is also one of the 6 official languages of the UN. In order to correctly understand the meanings of words in the Arabic language, it is necessary to be aware of their wide range of meanings. This aspect is considered in the article. Since there are many types of verbs in the Arabic language, we took verbs with two or three letters added to the regular verbs.